Pertanggungjawaban Pidana Pelaku Tindak Pidana Eksploitasi Seksual Anak: Tinjauan Terhadap Peraturan Perundangan - Zulkifli Ismail; Melanie Pita Lestari; Ahmad (KRTHA BHAYANGKARA, 2021)
The crime of sexual exploitation of children is a crime that never subsides even though the times are developing, as well as technology and human thought patterns have progressed. All criminal practices that result in degrading and threaten the physical and psychosocial integrity of children are included in the commercial sexual exploitation of children. The main issues that will be discussed in this study are how the form of the crime of child sexual exploitation and how the criminal responsibility of the perpetrators of the crime of sexual exploitation of children in terms of the existing laws and regulations in Indonesia. This study aims to identify and describe the forms of criminal acts of sexual exploitation of children and how the forms of criminal liability for perpetrators of crimes of child sexual exploitation as stated in the legislation. This study uses a normative juridical research method using a statutory approach. Based on the analysis conducted, it is known that Indonesia does not yet have legislation that specifically regulates this crime, so that in the future it is hoped that there will be a legislation that can specifically accommodate this crime.